Non solo petrolio: strategie per lo sviluppo sostenibile della Val d'Agri Not just oil: strategies for the sustainable development of the Val d'Agri - Giuseppe B. Las Casas (TRIA Urban Studies, 2019)
The local dimension of development, even in a framework of global relationships and interconnections, appears as a topic of great interest for the territorial planning disciplines, opening new spaces above all in the reflection on the effectiveness of large area and supra-municipal level planning. The Val d'Agri Inter-communal Structural Plan was conceived as an experimental model of inter-municipal plan, as per DGR n. 1495 of 21/09/2010 of the Basilicata Region, for the development of which a Memorandum of Understanding was signed between the administrations of 23 municipalities. Reference for the entire activity of technical and scientific support to the Staff of the Basilicata Region were three academic institutions: the School of Engineering (SI) of the University of Basilicata, the Department of European and Mediterranean Cultures (DiCEM) of the University of Basilicata, the Urban and Spatial Planning Laboratory "Raffaele D'Ambrosio" (LUPT) of the Federico II University of Naples After a first phase of the research work, concluded in 2014 and whose results are summarized in this volume, in 2018 the technical-scientific support activities have been resumed to allow the Region to define the eventual final products of the Inter-municipal Structural Plan of Val d'Agri.